The change in the dynamics of Costa Rica’s electoral set up: a case of dealignment Cambio en la dinámica electoral en Costa Rica: un caso de desalineamiento - Fernando SÁNCHEZ CAMPOS (América Latina Hoy, 2010)
The results of the last two general elections (1998 and 2002) in Costa Rica, suggest that the country’s electoral dynamics have exited their apparent stability and entered a process of change. The present study evaluates the main signs of this change (rising levels of absenteeism, ticket-splitting, electoral volatility, and support for third parties), and defines it as an «electoral dealignment» process. Moreover, it argues that there is evidence to conclude that electoral dealignment in Costa Rica seems to be a result of a process of «partisan dealignment». <span style="font-family: ";Times New Roman";; color: #1b171a; font-size: 8.5pt; mso-bidi-font-family: 'AJNKA P+ Simoncini Garamond'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-language: ES; mso-bidi-language: AR-SA;">Los resultados de las últimas dos elecciones generales (1998 y 2002) en Costa Rica sugieren que la dinámica electoral del país ha superado su aparente estabilidad para entrar en un proceso de cambio. El presente estudio evalúa las principales señales de este cambio (aumentos en los niveles de abstencionismo, quiebra del voto, volatilidad electoral y apoyo a terceros partidos), y lo define como un proceso de «desalineamiento electoral» <span style="font-family: ";AJNKC P+ Simoncini Garamond";; color: #1b171a; font-size: 8.5pt; mso-bidi-font-family: 'AJNKC P+ Simoncini Garamond'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-language: ES; mso-bidi-language: AR-SA;">(electoral dealignment)<span style="font-family: ";Times New Roman";; color: #1b171a; font-size: 8.5pt; mso-bidi-font-family: 'AJNKA P+ Simoncini Garamond'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-language: ES; mso-bidi-language: AR-SA;">. Además plantea que existe evidencia para concluir que este desalineamiento electoral pareciera ser el resultado de un proceso de «desalineamiento de partidos» <span style="font-family: ";AJNKC P+ Simoncini Garamond";; color: #1b171a; font-size: 8.5pt; mso-bidi-font-family: 'AJNKC P+ Simoncini Garamond'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: ES; mso-fareast-language: ES; mso-bidi-language: AR-SA;">(partisan dealignment).